Efficient Phantom Source Widening - Franz ZOTTER; Matthias FRANK (Archives of Acoustics, 2013)
We present a highly efficient filter structure to create power-complementary filter pairs for phantom source widening. It either introduces frequency-dependent phase or amplitude differences in a pair of loudspeaker signals. We evaluate how the perceptual effect is influenced by off-center listening positions in a standard 30 loudspeaker setup. The evaluation of the phantom source widening effect is based on measurements of the inter-aural cross-correlation coefficient (IACC), which is justified by its pronounced correlation to the perceived phantom source width in prior listening test results.